China : Accelerating Household Access to Clean Cooking and Heating - World Bank (Washington, DC, 2014)
The China Clean Stove Initiative (CSI), a collaborative effort of the Chinese government and the World Bank, aims to scale up access to clean cooking and heating stoves for poor, primarily rural households, who are likely to continue using solid fuels beyond 2030. More than half of China's population still relies on solid fuels (coal and biomass) for cooking and heating; many of these households, located mainly in rural areas, are likely to continue using solid fuels in the near future. Switching to modern energy alternatives would be the most effective way to achieve clean cooking and heating solutions and should be encouraged; yet such fuels are more expensive than solid fuels, requiring more costly stoves and delivery infrastructure. Effective strategies to scale up the dissemination of clean burning, fuel-efficient stoves for household cooking and heating can mitigate the health hazards associated with the burning of solid fuels. It is estimated that Household Air Pollution (HAP) from solid fuel use results in more than a million premature deaths each year in China. Scaled-up access to clean and efficient stoves is consistent with China's strategy to promote energy conservation, reduced carbon emissions, and green energy in villages. The China CSI comprises four phases: 1) initial stocktaking and development of the implementation strategy; 2) institutional strengthening, capacity building, and piloting of the strategy; 3) scaled-up program implementation; and 4) evaluation and dissemination of lessons learned. This report will serve as a knowledge base and roadmap to encourage and engage all interested parties in working together on this important agenda. The initial CSI stocktaking exercise calls for a comprehensive strategy comprising institutional strengthening and building of an enabling policy and regulatory environment, market and business development, and stimulation of household demand, supported by an innovative, results based financing approach.